Myeloid dendritic cells exhibit defects in activation and function in patients with multiple sclerosis - Haas, Jürgen; Schwarz, Alexander; Korporal-Kuhnke, Mirjam; Jarius, Sven; Wildemann, Brigitte (Journal of neuroimmunology, 2016)
Regulatory T cells (Tregs) are functionally defective in patients with multiple sclerosis (MS) and this dysfunction is related to an imbalanced composition of naïve and memory Treg subtypes. Several lines of evidence indicate that these abnormalities might result from a premature decline in thymic-dependent Treg neogenesis. Myeloid dendritic cells (mDCs) critically determine Treg differentiation in the thymus, and thymic stromal lymphopoietin receptor (TSLPR) expressed on mDCs is a key component of the signaling pathways involved in this process. TSLPR-expression on mDCs was previously shown to be decreased in MS. We hypothesized that functional alterations in mDCs contribute to aberrant Treg neogenesis and, in turn, to altered Treg homeostasis and function in MS. We recruited blood samples from 20 MS patients and 20 healthy controls to assess TSLPR expression on mDCs ex vivo by flow cytometry and by activating mDCs induced by recombinant TSLP (rhTSLP) in vitro. As previous studies documented normalization of both function and homeostasis of Tregs under immunomodulatory (IM) therapy with interferon-beta (IFN-beta) and glatiramer acetate (GA), we also tested phenotypes and function of mDCs obtained from IM-treated patients (IFN-beta: n=20, GA: n=20). We found that TSLP-induced mDC activation and effector function in vitro was reduced in MS and correlated with TSLPR-expression levels on mDCs. IM treatment prompted upregulation of TSLPR on mDCs and an increase in TSLP-induced activation of mDCs together with a normalization of Treg homeostasis. The decreased TSLP-induced activation of MS-derived mDCs in vitro, together with the reduced density of TSLPR on the cell surface of mDCs corroborates the hypothesis of mDCs being critically involved in impairing Treg development in MS.